Effect of lactic acid bacteria and Bacillus on anthracnose disease in postharvest papaya fruit - QUACH VAN CAO THI; TRAN QUOC DUNG; NGUYEN THI NHU HUYNH; NGUYEN TRUNG TRUC; NGUYEN PHUONG THUY (Society for Indonesian Biodiversity, 2023)
Abstract. Thi QVC, Dung TQ, Huynh NTN, Truc NT, Thuy NP. 2023. Effect of lactic acid bacteria and Bacillus on anthracnose disease in postharvest papaya fruit. Biodiversitas 24: 5883-5894. Anthracnose disease of papaya fruit caused by Colletotrichum (isolate TD1), identified by 5.8S rRNA sequence homology, is a main obstacle in papaya fruit, influencing fruit quality and minimizing shelf life. Therefore, to diminish the disease and sustain the fruit quality, the impact of Lactic Acid Bacteria (LAB) and Bacillus on the growth of anthracnose disease and fruit quality was investigated in vitro and in vivo. Furthermore, 13 LAB and 12 Bacillus isolates were collected from traditional fermented vegetables and papaya rhizospheric soils. The results showed that 13 LAB isolates and 6 isolates of Bacillus were inhibitory against Colletotrichum in an in vitro test. Two isolates of LDC11 and BHL21 with the highest antifungal activity were selected to evaluate their effect on Colletotrichum growth and papaya fruit quality under in vivo conditions. These findings indicated that the isolates LDC11 and BHL21 at a density of 106 CFU/mL reduced the disease incidence and severity. The LAB and Bacillus treated papaya fruit increased a number of parameters, such as weight loss, TSS, and L*, a*, and b* values. However, vitamin C content, TA, and fruit firmness were reduced compared to the control. The research shows a potential applications of LAB and Bacillus in the postharvest preservation of papaya fruit. To our knowledge, this is the first study to apply Bacillus and LAB bacteria to control diseases in postharvest papaya in Vietnam.